فاعلية الترجمة في تعليم اللغات الأجنبية وتحديات التعليم عن بعد، جامعة جيجل أنموذجا: The Efficiency Of Translation In Online Teaching Of Foreign Languages: Case Study: The Challenges Faced At Jijel University - Boukrous , Said; Bedjaoui, Wafa (Maalim, 2023)
The study aims to highlight the role of translation in foreign language acquisition to the languages student in the light of online teaching mode, by highlighting through this study, the most important difficulties, and then positive points to teach it via E-learning. The study found that the module of translation in languages departments is considered important and significant; it contributes to know and identify the differences between languages through comparing the two systems at the language version and structure level, The study also concludes through exploring the reality of teaching translation via online teaching to determine its relevance that it exists many difficulties, most notablythat: low standard training with student in computer applications use about this modeof education, in addition to the inerrability of evaluations and online exams operations.